The Influence of the Role of Village Apparatus, Competence of Village Fund Management Apparatus and Government Internal Control System on Village Fund Management Accountability (Study on Villages in Kumelembuai District) - Pingkan Claudia Juliana Pongantung; Inggriani Elim; Lidia M Mawikere (AFEBI Accounting Review, 2022)
This study aims to determine the effect of the role of the village apparatus, the competence of the village fund management apparatus, and the government's internal control system either partially or simultaneously on the accountability of village fund management in Kumelembuai District. This type of research is quantitative research with data collection methods, namely questionnaires filled out by respondents with a population of 101 and all of them are used as research samples. The data analysis method used was multiple linear regression using IBM SPSS 26. The results of this study shows that the government's internal control system has a positive and significant effect on the accountability of village fund management, while the role of village officials and the competence of the village fund management apparatus partially does not affect the accountability of village fund management.